Investment incentives and regional differentials in the Malaysian states - Ali, Hasnah; Golam Hassan, Asan Ali (World Business Institute, 2008)
Various investment incentives were seen to encourage industries to locate to the less developed areas so as to increase economic opportunity as well as monthly income, decrease poverty and unemployment. This strategy however has not been very successful and regional concentration tended to favour the more developed parts of the country and therefore most firms were still located in the more developed states. This is because of the high comparative advantages and economies of scale such as the establishment of manufacturing activities in those areas with easy access to infrastructure, service industries and large labor and consumer markets. This caused slow TFP growth and made convergent process in the less developed states remain problematic. This paper hopes to explore the investment incentives to encourage industries to be located to the less developed regions and analyses the extent of regional differentials and disparities in the regions and the need for regional development policy. The policy-makers need to think of ways and means to distribute the limited resources and increase the comparative advantage of the less developed states. References to secondary data and statistical analysis was used in the study